The Understanding of River and Community Resilience Studies in Perspective of Landscape Architecture - Mohd Firdaus, Rohana; Rasidi, Mohd Hisyam; Said, Ismail (Universitas Aisyiyah Yogyakarta, 2021)
River is part of community livelihood whereby its resilience protects it. However, river issues are still discussed, indicating opportunity and room for improvement. The social lens as perspective is also still lacking. Thereby, community resilience is adopted as approach looking at river. Hence, this paper explored the river and community resilience studies from social aspect. 129 articles based on online database were gathered, sieved and analysed. It was found that river and community resilience shares fields of fluvial geomorphology, sociology, ecology, urban planning and disaster risk. These fields have impacts in people-place relationship throughout humanity. Therefore, the community is responsible upon river and key to resilience.River is part of community livelihood whereby its resilience protects it. However, river issues are still discussed, indicating opportunity and room for improvement. The social lens as perspective is also still lacking. Thereby, community resilience is adopted as approach looking at river. Hence, this paper explored the river and community resilience studies from social aspect. 129 articles based on online database were gathered, sieved and analysed. It was found that river and community resilience shares fields of fluvial geomorphology, sociology, ecology, urban planning and disaster risk. These fields have impacts in people-place relationship throughout humanity. Therefore, the community is responsible upon river and key to resilience.